Asymmetric hydrogel electrolyte and preparation method thereof

By using double -layer asymmetric hydrogel electrolytes in the water -based zinc ion battery, combined with the hydrogel layer with high and low polymer network density, the problem of zinc branched crystal growth and side reactions is solved. Life and efficient energy storage.

CN119340507AActive Publication Date: 2025-01-21WUHAN UNIV

Patent Information

Application Number
CN202411393696.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-21
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

Existing aqueous zinc ion batteries are prone to form zinc dendrites and side reactions during charging and discharge, resulting in a decrease in energy storage efficiency and service life. While traditional hydrogel electrolytes improve the stability of zinc negative electrodes, it is difficult to maintain high ionic conductance. Rate.

Method used

A two-layer asymmetric hydrogel electrolyte is used. The hydrogel layer with high polymer network density provides mechanical properties and zinc ion flux uniformity, and the hydrogel layer with low polymer network density maintains high ionic conductivity.

Benefits of technology

Effectively inhibit zinc dendrite growth and side reactions, improve the cycle life of zinc-ion batteries, while maintaining fast reaction kinetics and excellent electrochemical energy storage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340507A_ABST
    Figure CN119340507A_ABST
Patent Text Reader

Abstract

The invention provides an asymmetric hydrogel electrolyte and a preparation method thereof, and belongs to the technical field of gel electrolytes. According to the invention, by constructing a hydrogel electrolyte layer with a high polymer network density and a low polymer network density, the asymmetric hydrogel electrolyte with the advantages of the two hydrogels is obtained, the hydrogel electrolyte layer with high polymer network density can provide good mechanical properties, reduce the activity of water molecules in the electrolyte, and help hydrated zinc ions to desolvate and homogenize the flux of the zinc ions; and the hydrogel electrolyte layer with low polymer network density can maintain relatively high ionic conductivity. The asymmetric hydrogel electrolyte can effectively inhibit dendritic crystal growth and side reaction of a zinc negative electrode of the zinc ion battery, so that the cycle service life of the zinc ion battery is prolonged, and meanwhile, the zinc ion battery can also keep rapid reaction kinetics, so that excellent electrochemical energy storage performance is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gel electrolytes, and in particular to an asymmetric hydrogel electrolyte and a preparation method thereof. Background Art

[0002] As the consumption of non-renewable energy such as oil, coal, and natural gas and the problem of environmental pollution increase, renewable clean energy (such as wind energy, solar energy, geothermal energy, tidal energy, etc.) has become the focus of subsequent development. Due to the instability of these clean energy power generation and the large difference between the power generation curve and the power consumption curve, it is urgent to develop low-cost, high-safety, efficient and environmentally friendly energy storage systems for power storage. Lithium-ion batteries dominate the global electrochemical energy storage market due to their high energy density, small size and long cycle life. However, lithium-ion batteries have shortcomings such as high cost, shortage of lithium ore resources, and low safety, which restrict their application in the field of large-scale energy storage.

[0003] In recent years, aqueous zinc-ion batteries have attracted widespread attention as a new type of energy storage system. They have the advantages of simple preparation, low cost, large theoretical capacity, high safety, and environmental friendliness. They are considered to be expected to replace lithium-ion batteries and become the main energy storage system for large-scale power grids in the future. However, during the charging and discharging process, zinc dendrites and side reactions are easily formed on the surface of the zinc metal negative electrode, resulting in a decrease in the energy storage efficiency and service life of zinc-ion batteries.

[0004] Developing new hydrogel electrolytes to replace aqueous electrolytes is an effective strategy to stabilize zinc negative electrodes and has received increasing attention in recent years. The cross-linked three-dimensional polymer network in the hydrogel electrolyte can provide good mechanical properties, reduce the activity of water molecules in the electrolyte, help desolvate hydrated zinc ions, and homogenize zinc ion flux, thereby effectively inhibiting zinc dendrite growth and side reactions and stabilizing the negative electrode of zinc ion batteries. Compared with traditional aqueous electrolytes, the tight three-dimensional polymer network of hydrogel electrolytes will inevitably reduce the transmission rate of zinc ions. Therefore, how to obtain a hydrogel electrolyte that takes into account the advantages of stabilizing the zinc negative electrode and maintaining high ionic conductivity is still a difficulty in the field of gel electrolyte technology. Summary of the invention

[0005] In view of the deficiencies of the above prior art, the present invention provides an asymmetric hydrogel electrolyte and a preparation method thereof. The overall idea of ​​the present invention is as follows: a double-layer asymmetric hydrogel electrolyte is prepared, and the two hydrogel layers have two different polymer network densities of high and low. Among them, the hydrogel electrolyte layer with a high polymer network density can provide good mechanical properties, reduce the activity of water molecules in the electrolyte, help desolvation of hydrated zinc ions and homogenize zinc ion flux; and the hydrogel electrolyte layer with a low polymer network density can maintain a higher ionic conductivity.

[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0007] In a first aspect, the present invention provides a method for preparing an asymmetric hydrogel electrolyte, comprising the following steps: constructing a hydrogel layer with a low polymer network density on the surface of a hydrogel layer with a high polymer network density to obtain an asymmetric hydrogel; immersing the asymmetric hydrogel in an aqueous electrolyte to obtain an asymmetric hydrogel electrolyte; the solid content of the hydrogel layer with a high polymer network density is 15% to 50%, and the solid content of the hydrogel layer with a low polymer network density is 2% to 8%.

[0008] Preferably, the raw materials of the hydrogel layer include matrix materials and / or functional materials.

[0009] Further preferably, the matrix material includes but is not limited to one or more of polyvinyl alcohol, polyethylene glycol, polyacrylic acid, polyacrylamide, polyurethane, cellulose, chitin, chitosan, gelatin, hyaluronic acid, and sodium alginate.

[0010] Further preferably, the functional material includes but is not limited to one or more of graphene oxide, carbon nanotubes, silver nanowires, MXene, MOF, COF, and cellulose derivatives.

[0011] Preferably, the thickness of the hydrogel layer with high polymer network density is 1 to 500 μm; the thickness of the hydrogel layer with low polymer network density is 10 to 1500 μm.

[0012] Further preferably, the thickness of the hydrogel layer with high polymer network density is 200 μm; the thickness of the hydrogel layer with low polymer network density is 800 μm.

[0013] Preferably, the gelation method of the hydrogel includes but is not limited to one of cyclic freezing, light-induced crosslinking, heat-induced crosslinking, ionic crosslinking, and electrodeposition.

[0014] Preferably, the aqueous electrolyte includes but is not limited to ZnSO 4 、ZnCl 2 、Zn(NO 3 ) 2 、Zn(Ac) 2 、Zn(OTf) 2 、MnSO 4 、MnCl 2 、Mn(Ac) 2 One or more of .

[0015] Preferably, the asymmetric hydrogel is immersed in the aqueous electrolyte for 2 to 72 h.

[0016] Further preferably, the asymmetric hydrogel is immersed in the aqueous electrolyte for 24 h.

[0017] In a second aspect, the present invention provides an asymmetric hydrogel electrolyte prepared by the method.

[0018] In a third aspect, the present invention provides an application of the asymmetric hydrogel electrolyte in a zinc ion battery, wherein the hydrogel layer with a high polymer network density is on the negative electrode side, and the hydrogel layer with a low polymer network density is on the positive electrode side.

[0019] Compared with the prior art, the present invention is beneficial in that:

[0020] The present invention obtains an asymmetric hydrogel electrolyte having the advantages of both a high polymer network density hydrogel electrolyte and a low polymer network density hydrogel electrolyte through structural design. The asymmetric hydrogel electrolyte of the present invention can maintain a high ion transmission rate while stabilizing the negative electrode of the zinc ion battery, thereby maintaining fast reaction kinetics. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the preparation process of asymmetric hydrogel electrolyte;

[0022] Figure 2 This is a physical picture of the asymmetric hydrogel electrolyte prepared in Example 1;

[0023] Figure 3 This is a physical picture of the stretching and twisting of the asymmetric hydrogel electrolyte prepared in Example 1;

[0024] Figure 4 The SEM images of the hydrogel electrolytes of Comparative Examples 1, 2, 3 and Examples 1 and 2 after drying; wherein, Figure 4 a is a SEM image of the hydrogel electrolyte of Comparative Example 1 after drying; Figure 4 b is a SEM image of the hydrogel electrolyte of Comparative Example 2 after drying; Figure 4 c is the SEM image of the hydrogel electrolyte of Comparative Example 3 after drying; Figure 4 d is a SEM image of the hydrogel electrolyte of Example 1 after drying; Figure 4 e is a SEM image of the hydrogel electrolyte of Example 2 after drying;

[0025] Figure 5 The mechanical properties of the hydrogel electrolytes of Examples 1 and 2 and Comparative Examples 1, 2 and 3; wherein, Figure 5 a is a graph showing the relationship between tensile strain and tensile stress of the hydrogel electrolytes of Examples 1 and 2 and Comparative Examples 1, 2 and 3, Figure 5 b is a comparison chart of the tensile strength of the hydrogel electrolytes of Examples 1 and 2 and Comparative Examples 1, 2 and 3;

[0026] Figure 6 is the ionic conductivity of the hydrogel electrolytes of Comparative Examples 1, 2, 3 and Examples 1 and 2;

[0027] Figure 7 The figures are the cycle stability test results of zinc symmetrical batteries assembled using the hydrogel electrolytes of Comparative Example 2 and Examples 1 and 2, and the surface SEM images of the zinc electrodes after the cycle tests; wherein, Figure 7 a is the cycle stability test result of the zinc symmetric battery assembled using the hydrogel electrolyte of Comparative Example 2; Figure 7 b is the cycle stability test result of the zinc symmetric battery assembled using the hydrogel electrolyte of Example 2; Figure 7 c is the cycle stability test result of the zinc symmetric battery assembled using the hydrogel electrolyte of Example 1; Figure 7 d is a SEM image of a zinc sheet of a zinc symmetric battery assembled using the hydrogel electrolyte of Comparative Example 2; Figure 7 e is a SEM image of a zinc sheet of a zinc symmetric battery assembled using the hydrogel electrolyte of Example 2; Figure 7 f is a SEM image of a zinc sheet of a zinc symmetric battery assembled using the hydrogel electrolyte of Example 1;

[0028] Figure 8 The chronoamperometric test results of the zinc symmetrical battery assembled using Comparative Example 2 and Examples 1 and 2;

[0029] Fig. 9 To utilize the electrochemical performance of the assembled zinc-manganese full battery of Comparative Example 2 and Examples 1 and 2; wherein, Fig. 9 a is the EIS curve of the full battery; Fig. 9 b is the full battery rate cycling performance result; Fig. 9 c is the charge and discharge cycle performance result. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The present invention provides a method for preparing an asymmetric hydrogel electrolyte, comprising the following steps: constructing a hydrogel layer with a low polymer network density on the surface of a hydrogel layer with a high polymer network density to obtain an asymmetric hydrogel; immersing the asymmetric hydrogel in an aqueous electrolyte to obtain an asymmetric hydrogel electrolyte; the solid content of the hydrogel layer with a high polymer network density is 15% to 50%, and the solid content of the hydrogel layer with a low polymer network density is 2% to 8%. Figure 1 Schematic diagram of the preparation process of asymmetric hydrogel electrolyte.

[0032] In some examples, the raw material of the hydrogel layer includes a matrix material and / or a functional material.

[0033] In some examples, the matrix material includes, but is not limited to, one or more of polyvinyl alcohol, polyethylene glycol, polyacrylic acid, polyacrylamide, polyurethane, cellulose, chitin, chitosan, gelatin, hyaluronic acid, and sodium alginate.

[0034] In some examples, the functional material includes, but is not limited to, one or more of graphene oxide, carbon nanotubes, silver nanowires, MXene, MOF, COF, and cellulose derivatives.

[0035] In some examples, the thickness of the hydrogel layer with high polymer network density is 1-500 μm; the thickness of the hydrogel layer with low polymer network density is 10-1500 μm.

[0036] In some examples, the gelation method of the hydrogel includes, but is not limited to, one of cyclic freezing, photoinduced crosslinking, thermally induced crosslinking, ionic crosslinking, and electrodeposition.

[0037] In some examples, the aqueous electrolyte includes but is not limited to ZnSO 4 、ZnCl 2 、Zn(NO 3 ) 2 、Zn(Ac) 2 、Zn(OTf) 2 、MnSO 4 、MnCl 2 、Mn(Ac) 2 One or more of .

[0038] In some examples, the asymmetric hydrogel is immersed in the aqueous electrolyte for 2 to 72 h.

[0039] In the following specific examples, unless otherwise specified, the polyvinyl alcohol used is type 1799, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0040] Example 1

[0041] An asymmetric hydrogel electrolyte, the preparation steps are as follows:

[0042] (1) Take 2 mL of cellulose nanofiber (CNF) aqueous suspension (10 mg / mL) and 2 mL of graphene oxide (GO) aqueous suspension (10 mg / mL) and add them to 1.6 mL of polyvinyl alcohol (PVA) aqueous solution (100 mg / mL). Stir (400 r / min) at 100 °C until 2 mL of the mixture remains. Pour the obtained PVA / CNF / GO mixture into a 10 cm×10 cm×0.1 cm mold and freeze it in a refrigerator for 8 h (-20 °C). Then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, a PVA / CNF / GO hydrogel layer with a high polymer network density is obtained.

[0043] (2) Take 2 mL of CNF aqueous suspension (10 mg / mL) and 4.2 mL of water and add them to 1.8 mL of PVA aqueous solution (100 mg / mL). Stir at room temperature for 1 h until completely mixed (400 r / min). Pour the obtained PVA / CNF aqueous solution onto the surface of the PVA / CNF / GO hydrogel layer with high polymer network density in the mold in step 1, put it in a refrigerator and freeze it for 8 h (-20 °C), then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, the PVA / CNF / GO-PVA / CNF asymmetric hydrogel is obtained after demolding.

[0044] (3) The prepared hydrogel was immersed in 2 M ZnSO 4 After 24 h in aqueous electrolyte, PVA / CNF / GO-PVA / CNF asymmetric hydrogel electrolyte was obtained. The actual picture of the PVA / CNF / GO-PVA / CNF asymmetric hydrogel electrolyte is shown in Figure 2 The PVA / CNF / GO-PVA / CNF asymmetric hydrogel electrolyte was subjected to stretching and twisting tests, and the results are shown in Figure 4 As shown, the results indicate that the hydrogel electrolyte can maintain its shape intact without being damaged during stretching and twisting, exhibiting excellent mechanical properties.

[0045] Example 2

[0046] An asymmetric hydrogel electrolyte, the preparation steps are as follows:

[0047] (1) Take 2 mL of CNF aqueous suspension (10 mg / mL) and add it to 1.8 mL of PVA aqueous solution (100 mg / mL). Stir at 100°C (400 r / min) until 2 mL of the mixture remains. Pour the obtained PVA / CNF mixture into a 10 cm×10 cm×0.1 cm mold and freeze it in a refrigerator for 8 h (-20°C). Then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, a PVA / CNF hydrogel layer with a high polymer network density is obtained.

[0048] (2) Take 2 mL of CNF aqueous suspension (10 mg / mL) and 4.2 mL of water and add them to 1.8 mL of PVA aqueous solution (100 mg / mL). Stir at room temperature for 1 h until completely mixed (400 r / min). Pour the obtained PVA / CNF aqueous solution onto the surface of the PVA / CNF hydrogel layer with high polymer network density in the mold in step 1, put it in a refrigerator and freeze it for 8 h (-20 ℃), then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, PVA / CNF-PVA / CNF asymmetric hydrogel is obtained after demolding.

[0049] (3) The prepared asymmetric hydrogel was immersed in 2 M ZnSO 4 After 24 h in aqueous electrolyte, PVA / CNF-PVA / CNF asymmetric hydrogel electrolyte was obtained.

[0050] Example 3

[0051] An asymmetric hydrogel electrolyte, the preparation steps are as follows:

[0052] (1) Take 4 mL of GO aqueous suspension (10 mg / mL) and add it to 3.6 mL of PVA aqueous solution (100 mg / mL). Stir at 100 °C (400 r / min) until 4 mL of the mixture remains. Pour the obtained PVA / CNF mixture into a 10 cm×10 cm×0.2 cm mold and freeze it in a refrigerator for 8 h (-20 °C). Then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, a PVA / GO hydrogel layer with a high polymer network density is obtained.

[0053] (2) Pour 16 mL of PVA aqueous solution (25 mg / mL) onto the surface of the PVA / GO hydrogel layer with high polymer network density in the mold in step 1, freeze it in a refrigerator for 8 h (-20 °C), then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, the PVA / GO-PVA asymmetric hydrogel is obtained after demolding.

[0054] (3) The prepared asymmetric hydrogel was immersed in 2 M ZnSO 4 After 24 h in aqueous electrolyte, PVA / GO-PVA asymmetric hydrogel electrolyte was obtained.

[0055] Example 4

[0056] An asymmetric hydrogel electrolyte, the preparation steps are as follows:

[0057] (1) Take 2 mL of PVA aqueous solution (100 mg / mL) into a 10 cm×10 cm×0.1 cm mold and freeze it in a refrigerator for 8 h (-20 °C), then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, a PVA hydrogel layer with a high polymer network density was obtained;

[0058] (2) Pour 16 mL of PVA aqueous solution (50 mg / mL) onto the surface of the PVA hydrogel layer with high polymer network density in the mold in step 1, freeze it in a refrigerator for 8 h (-20 °C), then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, demold it to obtain a PVA-PVA asymmetric hydrogel.

[0059] (3) The prepared asymmetric hydrogel was immersed in 2 M ZnSO 4 After 24 h in aqueous electrolyte, PVA-PVA asymmetric hydrogel electrolyte was obtained.

[0060] Example 5

[0061] An asymmetric hydrogel electrolyte, the preparation steps are as follows:

[0062] (1) Take 2 mL of cellulose nanofiber (CNF) aqueous suspension (10 mg / mL) and 2 mL of graphene oxide (GO) aqueous suspension (10 mg / mL) and add them to 1.6 mL of polyvinyl alcohol (PVA) aqueous solution (100 mg / mL). Stir (400 r / min) at 100 °C until 2 mL of the mixture remains. Pour the obtained PVA / CNF / GO mixture into a 10 cm×10 cm×0.1 cm mold and freeze it in a refrigerator for 8 h (-20 °C). Then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, a PVA / CNF / GO hydrogel layer with a high polymer network density is obtained.

[0063] (2) Take 2 mL of CNF aqueous suspension (10 mg / mL) and 4.2 mL of water and add them to 1.8 mL of PVA aqueous solution (100 mg / mL). Stir at room temperature for 1 h until completely mixed (400 r / min). Pour the obtained PVA / CNF aqueous solution onto the surface of the PVA / CNF / GO hydrogel layer with high polymer network density in the mold in step 1, put it in a refrigerator and freeze it for 8 h (-20 °C), then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, the PVA / CNF / GO-PVA / CNF asymmetric hydrogel is obtained after demolding.

[0064] (3) The prepared hydrogel was immersed in 2 M ZnSO 4 and 0.1 M MnSO 4 After being placed in the mixed aqueous electrolyte for 24 h, PVA / CNF / GO-PVA / CNF asymmetric hydrogel electrolyte was obtained.

[0065] Example 6

[0066] An asymmetric hydrogel electrolyte, the preparation steps are as follows:

[0067] (1) Take 2 mL of CNF aqueous suspension (10 mg / mL) and add it to 1.8 mL of PVA aqueous solution (100 mg / mL). Stir at 100°C (400 r / min) until 2 mL of the mixture remains. Pour the obtained PVA / CNF mixture into a 10 cm×10 cm×0.1 cm mold and freeze it in a refrigerator for 8 h (-20°C). Then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, a PVA / CNF hydrogel layer with a high polymer network density is obtained.

[0068] (2) Take 2 mL of CNF aqueous suspension (10 mg / mL) and 4.2 mL of water and add them to 1.8 mL of PVA aqueous solution (100 mg / mL). Stir at room temperature for 1 h until completely mixed (400 r / min). Pour the obtained PVA / CNF aqueous solution onto the surface of the PVA / CNF hydrogel layer with high polymer network density in the mold in step 1, put it in a refrigerator and freeze it for 8 h (-20 ℃), then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, PVA / CNF-PVA / CNF asymmetric hydrogel is obtained after demolding.

[0069] (3) The prepared asymmetric hydrogel was immersed in 2 M ZnSO 4 and 0.1 M MnSO 4 After being placed in the mixed aqueous electrolyte for 24 h, the PVA / CNF-PVA / CNF asymmetric hydrogel electrolyte was obtained.

[0070] Example 7

[0071] An asymmetric hydrogel electrolyte, the preparation steps are as follows:

[0072] (1) Take 2 mL of PVA aqueous solution (100 mg / mL) into a 10 cm×10 cm×0.1 cm mold and freeze it in a refrigerator for 8 h (-20 °C), then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, a PVA hydrogel layer with a high polymer network density was obtained;

[0073] (2) Pour 16 mL of PVA aqueous solution (25 mg / mL) onto the surface of the PVA hydrogel layer with high polymer network density in the mold in step 1, freeze it in a refrigerator for 8 h (-20 °C), then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, demold it to obtain a PVA-PVA asymmetric hydrogel.

[0074] (3) The prepared asymmetric hydrogel was immersed in 2 M ZnSO 4 After 24 h in aqueous electrolyte, PVA-PVA asymmetric hydrogel electrolyte was obtained.

[0075] Comparative Example 1

[0076] A conventional hydrogel electrolyte, the preparation steps are as follows:

[0077] (1) Take 2.5 mL of CNF aqueous suspension (10 mg / mL) and 5.25 mL of water and add them to 2.25 mL of PVA aqueous solution (100 mg / mL). Stir at room temperature for 1 h until completely mixed (400 r / min). Pour the obtained PVA / CNF aqueous solution into a 10 cm×10 cm×0.1 cm mold and freeze it in a refrigerator for 8 h (-20 ℃). Then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, PVA / CNF hydrogel was obtained after demolding.

[0078] (2) The prepared hydrogel was immersed in 2 M ZnSO 4 After 24 h in aqueous electrolyte, PVA / CNF hydrogel electrolyte was obtained.

[0079] Comparative Example 2

[0080] A conventional hydrogel electrolyte, the preparation steps are as follows:

[0081] (1) Take 5 mL of CNF aqueous suspension (10 mg / mL) and 0.5 mL of water and add them to 4.5 mL of PVA aqueous solution (100 mg / mL). Stir at room temperature for 1 h until completely mixed (400 r / min). Pour the obtained PVA / CNF aqueous solution into a 10 cm×10 cm×0.1 cm mold and freeze it in a refrigerator for 8 h (-20 ℃). Then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, PVA / CNF hydrogel was obtained after demolding.

[0082] (2) The prepared hydrogel was immersed in 2 M ZnSO 4 After 24 h in aqueous electrolyte, PVA / CNF hydrogel electrolyte was obtained.

[0083] Comparative Example 3

[0084] A conventional hydrogel electrolyte, the preparation steps are as follows:

[0085] (1) Take 10 mL of CNF aqueous suspension (10 mg / mL) and add it to 9 mL of PVA aqueous solution (100 mg / mL). Stir at 100 °C (400 r / min) until 10 mL of the mixture remains. Pour the obtained PVA / CNF aqueous solution into a 10 cm×10 cm×0.1 cm mold and freeze it in a refrigerator for 8 h (-20 °C). Then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, PVA / CNF hydrogel is obtained after demolding.

[0086] (2) The prepared hydrogel was immersed in 2 M ZnSO 4 After 24 h in aqueous electrolyte, PVA / CNF hydrogel electrolyte was obtained.

[0087] Comparative Example 4

[0088] A conventional hydrogel electrolyte, the preparation steps are as follows:

[0089] (1) Take 5 mL of CNF aqueous suspension (10 mg / mL) and 0.5 mL of water and add them to 4.5 mL of PVA aqueous solution (100 mg / mL). Stir at room temperature for 1 h until completely mixed (400 r / min). Pour the obtained PVA / CNF aqueous solution into a 10 cm×10 cm×0.1 cm mold and freeze it in a refrigerator for 8 h (-20 ℃). Then take it out and thaw it at room temperature for 4 h. After three freeze / thaw cycles, PVA / CNF hydrogel was obtained after demolding.

[0090] (2) The prepared hydrogel was immersed in 2 M ZnSO 4and 0.1 M MnSO 4 After being mixed in aqueous electrolyte for 24 h, the PVA / CNF hydrogel electrolyte was obtained.

[0091] The hydrogel electrolytes of Examples 1 and 2 and Comparative Examples 1, 2 and 3 were freeze-dried, and the morphology of the freeze-dried hydrogel electrolytes was characterized using SEM. The results are as follows: Figure 4 As shown, Figure 4 a is a SEM image of the hydrogel electrolyte of Comparative Example 1 after drying; Figure 4 b is a SEM image of the hydrogel electrolyte of Comparative Example 2 after drying; Figure 4 c is the SEM image of the hydrogel electrolyte of Comparative Example 3 after drying; Figure 4 d is a SEM image of the hydrogel electrolyte of Example 1 after drying; Figure 4 e is a SEM image of the hydrogel electrolyte of Example 2 after drying. Figure 4 It can be seen that the conventional hydrogel electrolyte in the comparative example has a uniform porous structure. As the polymer network density increases, the pore structure of the hydrogel becomes more compact, while the hydrogel of the present invention has an obvious asymmetric pore structure.

[0092] The hydrogel electrolytes of Examples 1 and 2 and Comparative Examples 1, 2 and 3 were subjected to tensile tests using a universal mechanical testing machine. The test results are as follows: Figure 5 As shown, Figure 5 a is a graph showing the relationship between tensile strain and tensile stress of the hydrogel electrolytes of Examples 1 and 2 and Comparative Examples 1, 2 and 3, Figure 5 b is a comparison chart of the tensile strength of the hydrogel electrolytes of Examples 1 and 2 and Comparative Examples 1, 2 and 3. Figure 5 It can be seen that the tensile strengths of the hydrogel electrolytes in Comparative Examples 1, 2, and 3 are 0.17 MPa, 0.47 MPa, and 0.74 MPa, respectively, indicating that with the increase of the polymer network density, the tensile strength of the hydrogel electrolyte is significantly improved; the tensile strengths of the asymmetric hydrogel electrolytes in Examples 1 and 2 are 0.43 MPa and 0.37 MPa, respectively. This is because the asymmetric hydrogel electrolytes in Examples 1 and 2 have a high polymer network density layer with high tensile strength. Therefore, the asymmetric hydrogel electrolytes in Examples 1 and 2 can still maintain good mechanical properties.

[0093] Electrochemical performance test

[0094] (1) Ionic conductivity test

[0095] The ionic conductivity of the hydrogel electrolytes of Examples 1 and 2 and Comparative Examples 1, 2 and 3 was tested and calculated. The test results are as follows: Figure 6 As shown. Figure 6 It can be seen that the ionic conductivity of the hydrogel electrolytes in Comparative Examples 1, 2, and 3 is 23.2 mS cm -1 、10.1 mS cm -1 、4.3 mS cm -1 , indicating that as the polymer network density increases, the ionic conductivity of the hydrogel electrolyte decreases significantly; the ionic conductivity of the asymmetric hydrogel electrolyte in Examples 1 and 2 is 16.2 mS cm -1 and 11.8 mS cm -1 This is because the asymmetric hydrogel electrolytes in Examples 1 and 2 have a low polymer network density layer. Therefore, the asymmetric hydrogel electrolytes in Examples 1 and 2 can still maintain a relatively high ionic conductivity.

[0096] (2) Activation energy test

[0097] The zinc symmetric battery was assembled using the hydrogel electrolytes of Examples 1 and 2 and Comparative Examples 1, 2 and 3, and the activation energy was tested and calculated to characterize the desolvation ability of hydrated zinc ions in the hydrogel electrolyte. The test results are shown in Table 1.

[0098] Table 1: Activation energy test results

[0099]

[0100] It can be seen from Table 1 that the activation energies of Comparative Examples 1, 2, and 3 are 28.1 KJ mol -1 , 22.7 KJ mol -1 、16.7 KJ mol -1 , indicating that the desolvation capacity of hydrated zinc ions in the hydrogel electrolyte increases significantly with the increase of polymer network density; the activation energies of Examples 1 and 2 are 19.2 KJ mol -1 and 21.0 KJ mol -1 This is because the asymmetric hydrogel electrolytes in Examples 1 and 2 have a high polymer network density layer. Therefore, the asymmetric hydrogel electrolytes in Examples 1 and 2 can still maintain excellent desolvation ability.

[0101] (3) Corrosion current test

[0102] Zinc symmetric batteries were assembled using the hydrogel electrolytes of Examples 1 and 2 and Comparative Examples 1, 2, and 3, and Tafel curve tests were performed. The corresponding corrosion currents were calculated to characterize the corrosion resistance of the zinc negative electrode in the hydrogel electrolyte. The test results are shown in Table 2.

[0103] Table 2: Corrosion current test results

[0104]

[0105] From Table 2, we can see that the corrosion currents of Comparative Examples 1, 2, and 3 are 0.60 mA cm -2 , 0.41 mA cm -2 , 0.15 mAcm -2 , indicating that as the polymer network density increases, the corrosion resistance of the zinc negative electrode is significantly improved; the activation energies of Examples 1 and 2 are 0.27 mA cm -2 and 0.33 mA cm -2 This is because the high polymer network density layer in the asymmetric hydrogel electrolyte in Examples 1 and 2 is in direct contact with the zinc negative electrode. Therefore, the zinc negative electrodes in Examples 1 and 2 maintain excellent corrosion resistance.

[0106] (4) Cyclic performance test of zinc symmetric battery

[0107] The zinc symmetric battery was assembled using the hydrogel electrolyte of Examples 1, 2 and Comparative Example 2, and the zinc symmetric performance test was performed to characterize the cycle stability of the zinc negative electrode in the hydrogel electrolyte. The test results are shown in Tables 3 and Figure 7 As shown in a~7c.

[0108] Table 3: Cycling performance test results of zinc symmetric battery

[0109]

[0110] From Table 3 and Figure 7 It can be seen that the stability of the zinc negative electrode using the conventional hydrogel electrolyte of Comparative Example 2 is poor and the cycle time is short; while the cycle life of the zinc negative electrode using the asymmetric hydrogel electrolyte of Examples 1 and 2 is significantly improved, indicating that the asymmetric structural design of the hydrogel electrolyte can significantly improve the stability of the zinc negative electrode.

[0111] The morphology of the zinc sheets in the zinc symmetric battery after 100 cycles was characterized by SEM. Figure 7 d~7f, where Figure 7 d is a SEM image of a zinc sheet of a zinc symmetric battery assembled using the hydrogel electrolyte of Comparative Example 2; Figure 7 e is a SEM image of a zinc sheet of a zinc symmetric battery assembled using the hydrogel electrolyte of Example 2; Figure 7 f is a SEM image of a zinc sheet of a zinc symmetric battery assembled using the hydrogel electrolyte of Example 1. Figure 7 From d~7f, it can be seen that the surface structure of the zinc sheet corresponding to comparative example 2 is uneven, with obvious zinc dendrites; while the surfaces of the zinc sheets corresponding to embodiments 1 and 2 are relatively smooth, indicating that the asymmetric hydrogel electrolyte can significantly inhibit the growth of zinc dendrites on the surface of the zinc negative electrode.

[0112] (5) Chrono current test

[0113] The zinc symmetric battery was assembled using the hydrogel electrolytes of Examples 1, 2 and Comparative Example 2, and a chronoamperometric test was performed at an overpotential of -150 mV to characterize the diffusion behavior of zinc ions in the hydrogel electrolyte. The test results are shown in FIG. Figure 8 As shown. Figure 8 It can be seen that the current of the battery assembled using the hydrogel electrolyte of Comparative Example 2 continues to increase, indicating that the zinc ions diffuse mainly in two dimensions in the hydrogel electrolyte; while the current of the battery assembled using the hydrogel electrolyte of Examples 1 and 2 remains stable after a short increase, indicating that the zinc ions diffuse mainly in three dimensions in the asymmetric hydrogel electrolyte, further indicating that the use of asymmetric hydrogel electrolytes can homogenize the zinc ion flux and inhibit uneven two-dimensional diffusion.

[0114] (6) Zinc-manganese full battery performance test

[0115] Manganese dioxide was used as the positive electrode material and zinc sheet was used as the negative electrode material. The hydrogel electrolytes of Examples 1, 2 and Comparative Example 2 were used as electrolyte and diaphragm to assemble zinc-manganese full batteries and conduct electrochemical energy storage performance tests to characterize the effect of the hydrogel electrolyte on the energy storage performance of zinc ion batteries. The test results are shown in FIG. Fig. 9 As shown, Fig. 9 a is the EIS curve of the full battery, Fig. 9 b is the full battery rate cycle performance result, Fig. 9 c is the charge and discharge cycle performance result. Fig. 9 It can be seen from a that the diameter of the semicircular ring in the EIS curve of the full battery corresponding to Examples 1 and 2 is smaller than that of Comparative Example 2, corresponding to a lower charge transfer resistance, indicating that the battery using the asymmetric hydrogel electrolyte has faster reaction kinetics; Fig. 9 b It can be seen that the full battery corresponding to Examples 1 and 2 has a higher capacity and a better rate performance. In addition, the charge and discharge cycle performance of the full battery was also tested. Fig. 9 c It can be seen that the full batteries corresponding to Examples 1 and 2 can still maintain 89.4% and 65.5% of the initial capacity after 800 charge and discharge cycles, showing good cycle stability, while the capacity retention rate of the battery corresponding to Comparative Example 2 is only 34.6%, indicating that the use of asymmetric hydrogel electrolytes can significantly improve the cycle stability of zinc ion batteries.

[0116] In summary, the present invention obtains a hydrogel electrolyte having the advantages of both hydrogels by constructing a hydrogel electrolyte layer with two different polymer network densities, high and low, in steps, wherein the hydrogel electrolyte layer with high polymer network density can provide good mechanical properties, reduce the activity of water molecules in the electrolyte, help desolvation of hydrated zinc ions and homogenize zinc ion flux; while the hydrogel electrolyte layer with low polymer network density can maintain a high ionic conductivity. The asymmetric hydrogel electrolyte of the present invention can effectively inhibit the dendrite growth and side reactions of the zinc negative electrode of the zinc ion battery, thereby improving the cycle life of the zinc ion battery, and the zinc ion battery can also maintain fast reaction kinetics, thereby showing excellent electrochemical energy storage performance.

[0117] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A method for preparing an asymmetric hydrogel electrolyte, characterized in that: The method comprises the following steps: constructing a hydrogel layer with a low polymer network density on the surface of a hydrogel layer with a high polymer network density to obtain an asymmetric hydrogel; immersing the asymmetric hydrogel in an aqueous electrolyte to obtain an asymmetric hydrogel electrolyte; the solid content of the hydrogel layer with a high polymer network density is 15% to 50%, and the solid content of the hydrogel layer with a low polymer network density is 2% to 8%.

2. The method for preparing an asymmetric hydrogel electrolyte according to claim 1, characterized in that: The raw materials of the hydrogel layer include matrix materials and / or functional materials.

3. The method for preparing an asymmetric hydrogel electrolyte according to claim 2, characterized in that: The matrix material includes, but is not limited to, one or more of polyvinyl alcohol, polyethylene glycol, polyacrylic acid, polyacrylamide, polyurethane, cellulose, chitin, chitosan, gelatin, hyaluronic acid, and sodium alginate.

4. The method for preparing an asymmetric hydrogel electrolyte according to claim 2, characterized in that: The functional material includes, but is not limited to, one or more of graphene oxide, carbon nanotubes, silver nanowires, MXene, MOF, COF, and cellulose derivatives.

5. The method for preparing an asymmetric hydrogel electrolyte according to claim 1, characterized in that: The thickness of the hydrogel layer with high polymer network density is 1 to 500 μm; the thickness of the hydrogel layer with low polymer network density is 10 to 1500 μm.

6. The method for preparing an asymmetric hydrogel electrolyte according to claim 1, characterized in that: The gelation method of the hydrogel includes, but is not limited to, one of cyclic freezing, light-induced crosslinking, heat-induced crosslinking, ion crosslinking, and electrodeposition.

7. The method for preparing an asymmetric hydrogel electrolyte according to claim 1, characterized in that: The aqueous electrolyte includes but is not limited to one or more of ZnSO4, ZnCl2, Zn(NO3)2, Zn(Ac)2, Zn(OTf)2, MnSO4, MnCl2, and Mn(Ac)2.

8. The method for preparing an asymmetric hydrogel electrolyte according to claim 1, characterized in that: The asymmetric hydrogel is immersed in the aqueous electrolyte for 2 to 72 hours.

9. An asymmetric hydrogel electrolyte prepared by the method according to any one of claims 1 to 8.

10. Use of an asymmetric hydrogel electrolyte prepared by the method according to any one of claims 1 to 8 in a zinc ion battery, characterized in that: In the asymmetric hydrogel electrolyte, the hydrogel layer with high polymer network density is on the zinc negative electrode side, and the hydrogel layer with low polymer network density is on the positive electrode side.

Citation Information

Patent Citations

  • Zwitterionic double network hydrogels

    CN112805033A

  • Asymmetric gel-state electrolyte as well as preparation method and application thereof

    CN113964381A

  • Double-layer gel electrolyte for aqueous zinc ion battery and preparation method of double-layer gel electrolyte

    CN116666777A

  • Zinc ion battery based on ionic liquid-aqueous gel double-layer electrolyte and preparation method thereof

    CN117594885A

  • Dual-network gel electrolyte, preparation method thereof and aqueous zinc ion battery

    CN118271521A

Cited By

  • Waterborne polyurethane gel electrolyte, preparation method thereof and zinc ion battery

    CN119890483A

  • An aqueous polyurethane gel electrolyte, its preparation method and a zinc ion battery

    CN119890483B